Kinerja Rantai Pasok Kedelai di Kabupaten Grobogan - Bubun Bubun; Sukardi Sukardi; Ono Suparno (School of Business, Bogor Agricultural University (SB-IPB), 2018)
The objectives of this study were to illustrate the structure of the soybean supply chain, to identify the performance of the soybean supply chain, and to recommend improvements in the form of managerial implications. This research used descriptive analysis method, and the analyzer used in this research was Supply Chain Operation References (SCOR). This study used primary data and secondary data. The primary data were obtained from direct observations, Focus Group Discussion (FGD), in depth interviews, and questionnaire whereas the secondary data were collected from literature study, farmer group data and agricultural statistical data from the Agriculture Department and Ministry of Agriculture. Based on the analysis of the supply chain structure, it was illustrated that there are two major parts of the supply chain structure, i.e. the short structure in which the breeder group acts as the main distributor, and the long supply chain structure in which the distribution pattern starts from the agent and dealer prior to reaching consumers. In general, the performance of the soybean supply chain in Grobogan Regency is reasonably good as it can be seen from the orders delivered to the customers and the perfect and in time order fulfillment as well as the suitability of the product with the increasing qualification standard. The order fulfillment cycle also can be adjusted with stock availability, and the supply chain flexibility can still be optimized when there is a sudden order, and supply chain costs can be covered from the sales of soybeans.Keywords: soybeans (Anguilla spp.), SCOR, supply chain, Grobogan District